Directional solidification of Ti-46Al-8Nb alloy in BaZrO3 coated Al2O3 composite mould. (November 2018) - Li, Kai; Xiong, Fuhao; Chen, Guangyao; Ali, Wajid; Lu, Xionggang; Li, Chonghe
Abstract: The Bridgman-type furnace was used for the directional solidification of Ti-46Al-8Nb (at.%) intermetallic alloy in Al2 O3 mould with BaZrO3 protective coating. The dissolution of BaZrO3 refractory material, the effects of the spiral selector, phase composition and microstructures were investigated. The results showed that a single crystal was prepared successfully at the outlet of the spiral part due to the effects of spiral selector. However, a large columnar grain with three small grains (near single crystal) was formed during the solidification process. The angle between the lamellar direction and the growth direction was about 45° in the directional growth area. The final microstructure of Ti-46Al-8Nb alloy consisted of TiAl (γ) and Ti3 Al (α2 ) and no BaZrO3 phase was found. The dissolved of shell elements Ba, Y, Zr and O in the DS sample were 24 ppm, 293 ppm, 4130 ppm, 3690 ppm, respectively. Highlights: The Ti-46Al-8Nb alloy was directionally solidified by means of BaZrO3 coated Al2 O3 mould. At the end of the crystal selection, a large grain can be obtained. The spiral part showed an excellent effect on grain selection. A large columnar grain with three small grains (near single crystal) was formed during the solidification process. The angle between the lamellar direction and growth direction was 45°. No BaZrO3 particles were detected in the microstructures. The Ba, Y and Zr contents in the sample were about 24, 293 and 4130 ppm. The average oxygen content was about 3690 ppm.